Pengaruh Servant Leadership Dan Budaya Organisasional Terhadap Kinerja Dimediasi Oleh Motivasi (Studi Pada Dinas Perumahan Rakyat Dan Kawasan Permukiman Kabupaten Kendal) - Yunita, Ika; Soliha, Euis (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to analyze the influence of Servant Leadership (X1) and Organizational Culture (X2) on Performance (Y2) with Motivation (Y1) as a mediating variable at Dinas Perumahan Rakyat dan Kawasan Permukiman Kabupaten Kendal. This study uses primary data obtained from respondents through questionnaires. The research population consisted of all employees at Dinas Perumahan Rakyat dan Kawasan Permukiman, totaling 72 people. The sampling method was carried out using Census Sampling. Data analysis techniques include validity, reliability, t-test and mediation tests using path analysis and Sobel test. Data analysis was carried out using SPSS 25,0. The results of hypothesis testing using Regression Analysis show that Servant Leadership and Organizational Culture partially have a positive and significant influence on Motivation. Servant Leadership and Organizational Culture partially have a positive and significant influence on Performance. Apart from that, this research also found that Motivation does not have a significant effect on performance and cannot mediate the influence of Servant Leadership and Organizational Culture on the performance of employees who work at Dinas Perumahan Rakyat dan Kawasan Permukiman.